COVID 19: Impetus for â€œCommunity Spiritsâ€ among Filipinos - Razon, Brando Cabigas (Indonesian Journal of Science and Technology, 2020)
Virus is a borderline between living and non-living things, not capable of reproduction but only do this process utilizing the machineries of a living cell. For most ordinary people in the Philippines, the corona virus that caused Corona Virus Disease in December 2019 (COVID 19) was not of big importance. The Philippine government was just observing the usual measure such as installing thermal screening in the airports to detect arriving passengers with flu. The virus continued to spread to the whole world. The continuous spread of the virus is the reason why mass media in print, in television, and other forms were used to educate people on how to prevent the spread of the virus. The Philippines positive cases were increasing almost exponentially. The Philippines government was getting more serious on the corona virus problem. President Rodrigo Duterte announced in the evening of March 12, 2020 of the month-long lock down of the whole Metro Manila from March 15 to April 14, 2020 as the country looks forward to contain the COVID 19. Land, domestic air and domestic sea to and from Metro Manila were suspended within the period. Social and religious activities that involved mass gathering were banned. Conferences, seminars and like activities were postponed and people were advised to stay at home. The lock down has brought about both negative and positive things to the government and to the people which can be observed commonly in every place. The negative things could fall into economic, social and psychological aspects. If corona virus brings negative and undesirable things in the community and in the Philippines, there are also positive things that sprouted. It is true indeed that a misfortune or a disaster to a place or persons can be an opportunity to others. Lots of things which are favorable and beneficial to many people and to the nature during the lock down which include economic, social and ecological aspects. The current situation brought by the corona virus that resulted to lock down implemented by the government of the Philippines gives an opportunity to learn the value of compassion and empathy in times of crisis. COVID 19 is bad, but people can also see the good effect of it. In the Philippines, people always boost the morale of our fellow Filipinos to unite in this battle to overcome this crisis and â€œtogether, we heal as oneâ€.